Research on IoT Security Defense Based on Honeypot Technology. Issue 1 (April 2021) - Wang, Zhenxia; Yu, Linlin
Abstract: With the expansion of the Internet and the increase in the number of end users, mobile terminals are vulnerable to hackers, computer viruses and other dangerous attacks. Honeypot technology is a highly deceptive security protection technology, which can run in a variety of networks and terminal systems with characteristic vulnerabilities deliberately. Meanwhile, honeypot technology can induce intruders to launch attacks. Therefore, the source of the attack can be captured to realize security defenses, protecting important system terminals from infringement. Moreover, by inducing the intruder to attack the honeypot terminal, it can not only delay the time to attack the real target, but also timely monitor, collect and analyze the attack behavior to provide support for dealing with unknown threats. So, in order to solve the problems of traditional methods and apply honeypot technology to the process of unknown threat defense of mobile terminal, an intelligent defense method is proposed in the paper for mobile terminal unknown threats based on honeypot technology. The results of comparative experiments prove that the method proposed in the paper has less underreporting of unknown threats, and can fully detect the source information, which can meet the needs of mobile terminals for effective defense against unknown threats.